Comparative Genomic Analysis of 19 Clinical Isolates of Tigecycline-Resistant Acinetobacter baumannii - Liu, Lin; Shen, Ping; Zheng, Beiwen; Yu, Wei; Ji, Jinru; Xiao, Yonghong (Frontiers in Microbiology, 2020)
To assess the genomic profiles of tigecycline (Tgc)-resistant Acinetobacter baumannii, including antibiotic resistance (AR) genes and virulence factors (VF), whole-genome shotgun sequencing was performed on 19 Tgc–resistant (TgcR) A. baumannii strains collected in a tertiary hospital during the early phase of clinical introduction of Tgc in China from late 2012 to mid-2014. Data from an average of 624 Mbp of sequence was generated on each bacterial genome, with Q30 quality of 90%, and an average coverage of 96.6%. TCDC-AB0715 was used as a reference genome. The genome sequences were annotated for functional elements including AR genes, VFs, genome islands and inserted sequences before they were comparatively analyzed. The antibiotic susceptibility phenotypes of the strains were examined by a broth microdilution method to determine the minimal inhibitory concentration (MIC) of strains against major clinical antibiotics. Thirty-three CARD-annotated ARGs were shared by all 19 TgcR strains, and 24 ARGs distributed differently among strains. A total of 391 VFs were found to be diversely distributed in all TgcR strains. Based on ARG number distribution, the 19 TgcR strains were divided into several groups. Highly differentiated genes included gpi, mphG, armA, msrE, adec, catB8, aadA, sul1, blaOXA-435, aph3i, and blaTEM-1, which may represent gene markers for TgcR A. baumannii sub-types. In addition, when compared with Tgc-sensitive (TgcS) strains collected during the same period, TgcR strains featured enrichment of ARGs including aph6id, aph3ib and teta. Compared with 26 other whole-genome sequences of A. baumannii deposited in GeneBank, TgcR strains in this study commonly lacked the EF-Tu mutation for elfamycin resistance. Phylogenetic analysis revealed a close evolutionary relationship between 19 TgcR strains and to isolates in East and Northeast China. In short, the comprehensive functional and comparative genomic analysis of 19 clinical TgcR A. baumannii strains isolated in the early stage of Tgc usage in China revealed their close phylogenetic relationship yet variable genetic background involving multiple resistance mechanisms, raising oncern regarding prediction and control of Tgc resistance in the clinic . Using a simple ARG or VF gene number diversity method and marker genes, TgcR strain sub-types can be identified.